2009
DOI: 10.1111/j.1600-0404.1990.tb01564.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of quantitative cisternography in normal pressure hydrocephalus

Abstract: Twenty‐five patients with normal pressure hydrocephalus (NPH) and 16 patients with cerebral atrophy were investigated by quantitative cisternography using anterior images of the head 3, 6 and 24 h after a lumbar injection of 200 MBq 99mTc DTPA (diethylene‐triamine‐penta‐acetic acid). The activity in the lateral ventricles, basal cisterns, hemispheric convexities and total intracranial region was measured. Ratios between these regions/quantities were calculated. Fifteen of the NPH patients improved while 10 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 21 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Other drug-induced movement disorders (myoclonus, tremor, and dystonia) were diagnosed after excluding secondary causes of the abnormal movements, temporal relation to starting the drug, and improvement of the abnormal movements after drug cessation. The diagnosis of normal pressure hydrocephalus (NPH) was based on the presence of the following symptoms and signs: (1) gait disturbance; (2) cognitive dysfunction, urinary disturbance, or both; (3) ventricular enlargement (Evans ratio > 0.31) without cortical atrophy on brain MRI; (4) intracranial pressure below 20 cm H 2 0, as measured by lumbar puncture; (5) ventricular filling and blockage of convexity flow on radionuclide cisternography; and (6) the absence of other neurological diseases that could explain the symptoms, such as progressive supranuclear palsy, corticobasal degeneration, or ventricular enlargement with cortical atrophy [8,11]. The diagnostic criteria for psychogenic movement disorders were adapted from Fahn and Williams [7].…”
Section: Methodsmentioning
confidence: 99%
“…Other drug-induced movement disorders (myoclonus, tremor, and dystonia) were diagnosed after excluding secondary causes of the abnormal movements, temporal relation to starting the drug, and improvement of the abnormal movements after drug cessation. The diagnosis of normal pressure hydrocephalus (NPH) was based on the presence of the following symptoms and signs: (1) gait disturbance; (2) cognitive dysfunction, urinary disturbance, or both; (3) ventricular enlargement (Evans ratio > 0.31) without cortical atrophy on brain MRI; (4) intracranial pressure below 20 cm H 2 0, as measured by lumbar puncture; (5) ventricular filling and blockage of convexity flow on radionuclide cisternography; and (6) the absence of other neurological diseases that could explain the symptoms, such as progressive supranuclear palsy, corticobasal degeneration, or ventricular enlargement with cortical atrophy [8,11]. The diagnostic criteria for psychogenic movement disorders were adapted from Fahn and Williams [7].…”
Section: Methodsmentioning
confidence: 99%
“…Larsson et al [20] performed radioisotope cisternography in normal pressure hydrocephalus patients by lumbar injection of 200MBq99mT DTPA (diethylene-triamin-penta-acetic acid), and observed that the increased ratio between ventricular and total intracranial activity which suggested increased CSF reflux into the ventricles, and that ratio between ventricular and total intracranial activity was maintained at a steady level according to progression of time, suggesting that CSF absorption occurs at the ventricular wall to the periventricular tissues. Thereafter, the energy of the reflux pulsatile CSF flow into the ventricle exits via the ventricle wall into the brain parenchyme, resulting in collision with the brain parenchyme pulsation, reduced brain parenchyme compliance, and increased brain parenchyme pulse pressure.…”
mentioning
confidence: 99%
“…One of the important aspects in the formation of lateral ventricle dilatation in communicating hydrocephalus is the increased reverse pulsatile CSF flow to the lateral ventricle and the increased absorption of CSF by the lateral ventricle, and which has been proven by radioisotope cisternography techniques [18][19][20]. Larsson et al [20] performed radioisotope cisternography in normal pressure hydrocephalus patients by lumbar injection of 200MBq99mT DTPA (diethylene-triamin-penta-acetic acid), and observed that the increased ratio between ventricular and total intracranial activity which suggested increased CSF reflux into the ventricles, and that ratio between ventricular and total intracranial activity was maintained at a steady level according to progression of time, suggesting that CSF absorption occurs at the ventricular wall to the periventricular tissues.…”
mentioning
confidence: 99%
“…Lucency refers to hypodense areas, especially around the horns of the lateral ventricles. After injecting a radioactive tracer into the lumbar space, it is commonly seen that the tracer accumulates in the ventricles, providing indirect evidence that CSF is absorbed into the brain parenchyma [ 27 ].…”
Section: Transependymal Csf Flowmentioning
confidence: 99%